Effect of different methods for estimation of evapotranspiration and water deficit in soil on the growth rates of conilon clonal coffee - Gaspar Schwan, Matheus; Brioschi Andreão, Gabriel; Carolo Freitas, Maria Eduarda; Steill de Oliveira, Pedro Henrique; Fialho dos Reis, Edvaldo (Revista Brasileira de Engenharia de Biossistemas, 2023)
The water deficit is considered one of the main problems in coffee culture around the world. As a way to get around this problem, producers all over the world adopt the practice of irrigation. However, in the most cultivated areas, a rational irrigation management is not carried out, resulting in excessive or insufficient applications. Based on this, the present work aimed to evaluate the effect of different methods of evapotranspiration estimative and water deficit levels on the growth rates of the clonal conilon coffee. The experiment was conducted in a greenhouse, in a 2 x 3 factorial scheme with the factor evapotranspiration in 2 levels (Penman-Monteith (PM) and Hargreaves & Samani (HS), and the factor water deficit in 3 levels (80%, 50% and 30% of Evapotranspiration of Reference (ETo)) in a completely randomized design. From the results obtained, it was observed that the evapotranspiration estimation method and the water deficit levels had an effect on the growth rates and free assimilation rate of the clonal conilon coffee tree, with the highest growth values in plants irrigated with 80% of ETo by the HS method, and higher assimilation values in plants irrigated with 80% of ETo by the PM method.